Hilangnya Minat Generasi Muda dalam Keberlanjutan Industri Rumahan Gula Merah (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is an agricultural country, the plantation sub-sector provides an important role for the national economy. Coconut commodity is one of the big commodities. Wuluhan sub-district has a large potential for coconut plantations, when compared to other areas in Jember. The large use of coconut sap by the Lojejer community has made this village a Center for the Brown Sugar Industry. As time goes by, the brown sugar home industry in Lojejer village is decreasing. The absence of regeneration makes the number of existing home industries decrease. The purpose of this research is to find out the change in interest of the younger generation in the brown sugar cottage industry in Lojejer village by using qualitative methods and a phenomenological approach is used to understand how individual views or experiences are so that they are not interested or change in interest in continuing the existing cottage industry. factors that cause changes in interest in the younger generation in the existing brown sugar home industry, high work risk factors are one of them, tapping coconut sap which still uses traditional methods there is no guarantee of safety obtained with income that is not appropriate. The younger generation prefers to work in other sectors with lower work risks and prefers to work in sectors that provide more certain income benefits. Not a few of the youth who prefer to work as fishermen. The role of the government in providing socialization in using appropriate personal protective equipment to minimize work accidents among coconut sap tappers is urgently needed. The younger generation with their thoughts and knowledge of technology is expected to be able to contribute to the sustainability of the brown sugar processing process.